EU Municipal Organic Wastes Management and Its Implementation Prospects in Ukraine - Melnyk Olena (Sciendo, 2021)
The article focuses on the issue of the prospects of municipal organic wastes management in Ukraine in the context of the applicable EU practices in the field. The investigation was made according to the SWOT analysis. The general scientific and specific scientific methods were used at all the three stages of the investigation. The peculiarities of the Ukrainian legislation and their compliance with the EU directives and policies were analysed. The key problems of the Ukrainian wastes legislation, political and legal relations in the field were reviewed. The New Ukrainian Wastes Management Strategy was analysed. The main principles and priorities of the EU wastes strategies were presented. The best (and the most applicable for Ukraine) European practices were examined, including the five-step hierarchy and features of the national wastes collecting, sorting and disposal systems. Wastes composting technologies were discussed in detail. Possibilities of using wastes as bio fuel for refuelling municipal equipment, air transport, etc. were determined. The futility of expanding landfill areas for solving wastes management issues was noted. The main requirements to be met for regulating wastes management market in accordance with the Association Agreement with the EU were outlined. Recommendations on implementing circular economy principles and extended producers’ responsibility to encourage the public society to sort wastes, businesses to minimize wastes generation and draw interest to recycling were suggested.